Non-enzymatic and enzymatic antioxidant components of the mature Cambuí metabolism - Lailla Sabrina Queiroz Nazareno; Maria Raquel Alcântara de Miranda; Maria Ketully Neyane Alves Pinto; Mônica Maria Almeida Lopes; Maria do Socorro Moura Rufino (Acta Agronómica)
The objective of this work was to identify and evaluate the bioactive compounds, as well as the antioxidant potential, present in mature fruits of cambuizeiro (Myrcia multiflora) from the Chapada do Araripe, Brazil.  In the fruits were evaluated: vitamin C, total anthocyanins, yellow flavonoids, total polyphenols, total antioxidant activity by the FRAP, DPPH and ABTS methods, and the antioxidant superoxide dismutase (SOD) and catalase (CAT) activity.  Cambui had an average vitamin C content of 56.40 mg/100 g, 2869.44 mg/100 g total anthocyanins 2858.50 mg/100 g yellow flavonoids and 1007.64 mg EAG/100 g of total polyphenols.  While the total antioxidant activity according to FRAP method was 123.94 μM ferrous sulphate/g, DPPH was 1805.66 g/g EC50, and ABTS was 32.62 μM trolox/g.  The enzymatic activity of SOD was 846,203 AU/g, while CAT did not read.  These results indicate that the mature fruits of cambuizeiro present high antioxidant potential, corroborating to the idea that their consumption may result in benefits to human health.